Gluten-free snacks based on brown rice and amaranth flour with incorporation of cactus pear peel powder: Physical, nutritional, and sensorial properties - Miranda D.V. (2018)
The authors are grateful to the Laboratory of Process Engineering, Faculty of Agricultural Sciences, Universidad Nacional de Trujillo, and to Cienciactiva for the M.L. Rojas Ph.D. (CONCYTEC, Peru; Contract 087-2016-FONDECYT) scholarship from ‘‘Consejo Nacional de Ciencia, Tecnología e Innovación Tecnológica.”